Prediction of surgical resectability after FOLFIRINOX chemotherapy for borderline resectable and locally advanced pancreatic cancer (PeRFormanCe): a multicenter prospective trial - trial protocol - Luís Filipe Abreu de Carvalho; Filip Gryspeerdt; Wim Ceelen; Karen Geboes; Suzane Ribeiro; Anne Hoorens; Nele Vandenbussche; Kathleen B.M. Claes; Clarisse Lecluyse; Aliaksandr Anisau; Johan Van Ongeval; Willem Lybaert; et al. (BMC Surgery)
Abstract Background Neoadjuvant chemotherapy is used in borderline resectable (BR) and locally advanced (LA) pancreatic ductal adenocarcinoma (PDAC) to increase resection rate and improve cancer outcome. However, there is a need for better prediction of resectability. The aim of this prospective, single arm study is to improve prediction of surgical resection by using radiomics and liquid biopsy. Methods In this multicentric trial, 45 patients with BR or LA PADC will undergo neoadjuvant chemotherapy with FOLFIRINOX. An intention to treat analysis will be performed. The primary endpoint is the accuracy of the prediction of surgical resection. Secondary endpoints are overall survival and disease-free survival from the date of diagnosis, R0 and R1 resection rates, histopathological response, postoperative complications, patient reported outcomes with quality of life and health economic analysis. Translational research with multi-omics and radiomics based on computed tomography and magnetic resonance imaging aims to identify factors predictive of surgical resectability and survival. The primary hypothesis is that these strategies can increase the accuracy of predicting surgical resection. Discussion Improved prediction of resectability is necessary in BR and LA PDAC. We aim to investigate whether a combination of clinical, radiological, and multi-omics profiling in liquid biopsies can successfully predict resectability and thus optimize the therapeutic decision tree. Trial registration ClinicalTrials.gov Identifier: NCT05298722. Date of registration: March 28, 2022.